How are private school enrolment patterns changing across Indian districts with a growth in private school availability?. (2nd September 2016) - Chudgar, Amita; Creed, Benjamin
Abstract: The private school sector in India has grown significantly but the equity implications of this growth are not well understood. Traditionally private schools have been patronised by more educated and better-off families. Evidence also suggests a preference for enrolling male children in private schools. With the growth in the private school sector it is unclear whether these conventional patterns of private enrolment are changing. The (uneven but ongoing) implementation of the Right to Education (RTE) Act will likely create further opportunities for private school access. If research finds that access to the private sector remains uneven across the society in spite of this growth, then it may offer a note of caution against relying on private provision, and it may also provide an indication of the potentially significant and continued importance of public provision of education. In this paper we use district-level data from 2005–2006 and 2011–2012 to estimate how private enrolment patterns have changed alongside an appreciable growth in number of private schools. While 2011–2012 is too soon to evaluate the impact of RTE (as most states were still drafting rules and regulations) we identify states that eventually adapted clearer RTE regulations to investigate if private school enrolment patterns were changing differently in these states. The data show that a large growth in the private sector has not made patterns of private school enrolment more equitable in rural areas. In urban districts the data indicate a declining caste gap in private enrolment and a decline in the private enrolment gap between poor and non-poor students in states which eventually went on to adopt clearer RTE regulations.